Gender differences in the relationship between cardiometabolic index and all-cause and specific mortality in the United States adults: a national study - Li, Tianshu; Zhou, Haoran; Zhou, Hua (Frontiers in Endocrinology, 2025)
BackgroundThe cardiometabolic index (CMI) is a new comprehensive measure that reflects visceral obesity and metabolic function. This study aimed to examine associations between CMI and adult mortality from all causes and specific causes, as well as gender differences, using the National Health and Nutrition Examination Survey (NHANES) database.MethodsWe included 37,539 adult participants with complete data from the 1999-2018 NHANES database. We categorized the participants according to gender and constructed three models to investigate the relationship between CMI and the outcome variables. These were analyzed using Kaplan-Meier curve analysis, COX proportional risk models, and restricted cubic spline (RCS).ResultsBaseline characteristics showed that among both male and female participants, those who died exhibited higher levels of CMI compared to those who survived. Kaplan-Meier curves showed an increasing trend in all-cause and specific mortality with increasing follow-up time. When CMI was categorized according to quartiles (Q1-Q4), the probability of survival was lower in the Q4 group compared to Q1. We found no gender differences between all three mortality rates. In COX regression analyses, all-cause, cardiovascular, and diabetes mortality were significantly higher in Q4 in the whole population and female participants, whereas no significant differences were identified among male participants. The RCS showed a nonlinear positive correlation in diabetes mortality for females and a linear positive correlation in all-cause and cardiovascular mortality. As for males, CMI was positively and nonlinearly associated with all-cause and diabetes mortality. Besides, there is no statistically significant correlation for males in cardiovascular mortality.ConclusionThere were gender differences in the correlation between CMI and all-cause mortality, cardiovascular mortality, and diabetes mortality in the adult population. The findings indicated that adult females with elevated CMI levels were at an elevated risk of mortality from all causes, cardiovascular disease, and diabetes. At the same time, there were no significant associations in adult males.